The effects of tapering on performance in elite endurance runners: a systematic review - Grivas, G. V. (International Journal of Sports Science, 2018)
The purpose of this study was to perform a systematic review determine the effects of tapering on performance in elite endurance runners. The taper is a key element of the physical preparation of athletes in the weeks before a competition and it seems that the most important variable for maximize performance is training volume, training frequency and intensity. Three electronic databases were searched for original research articles. Nine studies met the inclusion criteria. The training volume is exponentially decreased by 17.6-85%. Two of studies showed that improve VO2max, whereas the other 4 studies found maintenance of VO2max. Six of the 9 included studies showed to improve the performance, two studies didn`t find significant changes of performance and one study found reduces of performance. Four of studies found reductions in training frequency and the five remaining studies showed a maintenance of training frequency.